2006
DOI: 10.1124/jpet.106.104380
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multitargets in Paeoniflorin-Induced Preconditioning

Abstract: Paeoniflorin (PF) is the principal component of Paeoniae radix prescribed in traditional Chinese medicine. The delayed neuroprotection induced by PF preconditioning and its underlying mechanisms were investigated in rat middle cerebral artery occlusion (MCAO) and reperfusion model. At a dosage of 20 or 40 mg/kg, PF preconditioning 48 h before MCAO followed by 24-h reperfusion significantly reduced the mortality and infarct volume and reversed the neurological deficits caused by ischemia. Likewise, the ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…For instance, Paeoniflorin (PF), the principal component of Paeoniae radix (used in traditional Chinese medicine), displays a preconditioning neuroprotective effect against cerebral ischemia in mice. The related mechanism has been shown to involve multiple factors including the adenosine 1 receptor/regulator of G protein/K ATP signaling, the arachidonic acid cascade, the nitric oxide system, neuronal damage markers, molecules related to mitochondrial damage, mitogen-activated protein kinase, as well as the nuclear factor-ÎșB pathway [73] . Pretreatment with another herb extract from Choto-san (Gouteng-san), a traditional Kampo medicine, also exhibits antidementia effects and neuroprotection against ischemia when administered at an appropriate dosage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Paeoniflorin (PF), the principal component of Paeoniae radix (used in traditional Chinese medicine), displays a preconditioning neuroprotective effect against cerebral ischemia in mice. The related mechanism has been shown to involve multiple factors including the adenosine 1 receptor/regulator of G protein/K ATP signaling, the arachidonic acid cascade, the nitric oxide system, neuronal damage markers, molecules related to mitochondrial damage, mitogen-activated protein kinase, as well as the nuclear factor-ÎșB pathway [73] . Pretreatment with another herb extract from Choto-san (Gouteng-san), a traditional Kampo medicine, also exhibits antidementia effects and neuroprotection against ischemia when administered at an appropriate dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of Si-Ni-San are Radix Bupleuri Chinensis (Chaihu), Radix Paeoniae Alba (Shaoyao), Fructus Citri Aurantii (Zhishi), and Radix Glycyrrhizae Uralensi (Gancao), with saikosaponin, paeoniflorin, naringin and glycyrrhizin as major active ingredients (Yamamoto et al,1975;Takagi and Harada,1969;Rouseff et al, 1987;Nikitina, 1966). Among these ingredients, paeoniflorin has been widely investigated as an antioxidant, cognitive enhancer, endotheliumdependent vasodilator, and neuroprotective agent (Goto et al, 1996;Ryu et al, 2001;Tabata et al, 2001;Chen et al, 2006). However, the actual contribution of paeoniflorin in Si-Ni-San against contact dermatitis, a typical T cell-mediated DTH response, remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…We found that TGP treatment prevented the reduction of BDNF in the lumbar spinal cord of EAE mice. The similar effect of TGP also occurred in rat middle cerebral artery occlusion and reperfusion model which shows the upregulated BDNF expression in the brain by PF preconditioning (Chen et al, 2006). CNPase is one of the most abundant proteins in CNS myelin and a possible auto-antigen in MS (Rosener et al, 1997).…”
Section: Discussionmentioning
confidence: 85%